New Recombinant Antimicrobial Peptides Confer Resistance to Fungal Pathogens in Tobacco Plants - Khademi, Mitra; Varasteh-Shams, Marzieh; Nazarian-Firouzabadi, Farhad; Ismaili, Ahmad (Frontiers in Plant Science, 2020)
Antimicrobial peptides have been long known to confer resistance to plant pathogens. In this study, new recombinant peptides constructed from a dermaseptin B1 (DrsB1) peptide fused to a chitin-binding domain (CBD) from Avr4 protein, were used for Agrobacterium tumefaciens-mediated transformation of tobacco plants. Polymerase chain reaction (PCR), semi‐quantitative RT‐PCR and western blotting analysis demonstrated the incorporation and expression of transgenes in tobacco genome and transgenic plants, respectively. In vitro experiments with recombinant peptides extracted from transgenic plants demonstrated a significant (P<0.01) inhibitory effect on the growth and development of plant pathogens. The DrsB1-CBD recombinant peptide had the highest antifungal activity against fungal pathogens. The expression of the recombinant peptides greatly protected transgenic plants from Alternaria alternata, Alternaria solani, Fusarium oxysporum and Fusarium solani fungi, in comparison to Pythium sp. and P. aphanidermatum. Expression of new recombinant peptides resulted in a delay in the colonization of fungi and appearance of fungal disease symptoms from six days to more than seven weeks. Scanning electron microscopy images revealed that the structure of the fungal mycelia appeared segmented, cling together, and crushed following the antimicrobial activity of the recombinant peptides. Greenhouse bioassay analysis showed that transgenic plants were more resistant to Fusarium and Pythium infections as compared with the control plants. Due to the high antimicrobial activity of the recombinant peptides against plant pathogens and novelty of recombinant peptides, this report shows the feasibility of this approach to generate disease resistance transgenic plants.